Tropical Pyomyositis - Chattopadhyay, Bitoti (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Tropical pyomyositis is characterized by suppuration within skeletal muscles, manifesting as single or multiple abscesses. Though primarily a disease of tropics, it is increasingly being reported from temperate regions in immunosuppressed patients. However, India has only few sporadic case reports. AIMS: The aim of this study is to evaluate the causative organisms, clinical presentations, diagnostic modalities, treatment protocols and outcome data in tropical pyomyositis patients. SUBJECTS AND METHODS: The study was carried out in Nilratan Sircar Medical College and Hospital, Kolkata over 3 years (July 2010 to June 2013). A total of 12 patients were diagnosed with tropical pyomyositis (confirmed with aspiration and culture of pus from muscle). All the investigation and treatment data were recorded systematically. RESULTS: The presenting feature was high fever and myalgia in all 12 patients. Quadriceps femoris was the most commonly involved muscle (50%); followed by iliopsoas (25%). Culture of the aspirate showed Staphylococcus aureus in nine patients (75%), Klebsiella pneumonia in one patient (8.33%) and no growth in two patients (16.67%) even after tubercular and fungal culture. CONCLUSIONS: Tropical pyomyositis can affect immune-competent individuals. S. aureus is the most commonly cultured organism. Immediate initiation of appropriate antibiotics and surgical debridement are required to avoid complications. The prognosis remains excellent if promptly treated.